2019
DOI: 10.1111/jcmm.14439
|View full text |Cite
|
Sign up to set email alerts
|

Maternal voluntary exercise mitigates oxidative stress and incidence of congenital heart defects in pre‐gestational diabetes

Abstract: Women with pre‐gestational diabetes have a higher risk of producing children with congenital heart defects (CHDs), caused predominantly by hyperglycemia‐induced oxidative stress. In this study, we evaluated if exercise during pregnancy could mitigate oxidative stress and reduce the incidence of CHDs in the offspring of diabetic mice. Female mice were treated with streptozotocin to induce pre‐gestational diabetes, then mated with healthy males to produce offspring. They were also given access to running wheels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…Activation and phosphorylation of eNOS-Ser1177 in the heart is mediated by Akt activation. As Akt activation has been shown to promote cardiomyocyte proliferation and expansion of cardiac progenitors [203], this pathway may also have contributed to protection against CHD pathogenesis observed in our model [16]. As of now, fetal adaptations in response to maternal exercise has not been well characterized.…”
Section: Maternal Exercise Reduces Incidence Of Chds From Pregestamentioning
confidence: 98%
See 2 more Smart Citations
“…Activation and phosphorylation of eNOS-Ser1177 in the heart is mediated by Akt activation. As Akt activation has been shown to promote cardiomyocyte proliferation and expansion of cardiac progenitors [203], this pathway may also have contributed to protection against CHD pathogenesis observed in our model [16]. As of now, fetal adaptations in response to maternal exercise has not been well characterized.…”
Section: Maternal Exercise Reduces Incidence Of Chds From Pregestamentioning
confidence: 98%
“…Remarkably, maternal voluntary exercise for 3 months before conception has recently been shown to lower the incidence of VSDs in offspring of old mothers, suggesting maternal exercise reduces the risk of CHDs associated with maternal age [191]. Using a STZ diabetes mouse model, we examined the effects of maternal exercise on pathogenesis of CHDs induced by pregestational diabetes [16]. Our results show that maternal exercise reduces ROS levels and oxidative stress and improves eNOS phosphorylation in the fetal hearts of offspring from mice with diabetes.…”
Section: Maternal Exercise Reduces Incidence Of Chds From Pregestamentioning
confidence: 99%
See 1 more Smart Citation
“…An allocation concealment was performed to hide the method of sorting trial participants into treatment groups. Strict diet control was applied to all participants, as follows: (1) a diet plan based on the patient's basic condition [26]; (2) monitoring of blood glucose; (3) calculation of the daily calorie requirement according to the patient's weight and making of an individual-compliant dietary plan to control dietary uptake; (4) advocacy of small meals and optimization of the dietary structure to ensure a balanced energy supply; and (5) scientific and rational exercise [27]. After middle pregnancy, 550 patients were determined with GDM and evenly assigned into the intervention group (received 500 mg cod-liver oil in capsule form daily) and control group (received placebo).…”
Section: Patientmentioning
confidence: 99%
“…In addition, the beneficial effect of physical activity was also proven using different in vivo animal models. So far, it was demonstrated that aerobic exercise decreased the production of reactive oxygen species (ROS) and oxidative stress in the fetal heart and minimized the risk of congenital heart defects via modulation of specific gene expression, in pre-gestational diabetes (Saiyin et al, 2019). Also, it is well known that physical activity leads to a decrease in glycemia, decreasing body weight and visceral adipose tissue and, at the same time, increasing insulin sensitivity.…”
Section: Type:  Aerobicmentioning
confidence: 99%